2018
DOI: 10.1177/1066896918768043
|View full text |Cite
|
Sign up to set email alerts
|

Poorly Differentiated Chordomas Showing Loss of INI1/SMARCB1: A Report of 2 Rare Cases With Diagnostic Implications

Abstract: Poorly differentiated chordomas are rare musculoskeletal tumors. Case 1. A 42-year-old lady presented with quadriparesis of 2 months' duration. Radiologic imaging disclosed a soft tissue mass in her left prevertebral- and paravertebral cervical region. Case 2. A 4-year-old male child presented with neck pain and restricted head movements of 1-year duration. Radiologic imaging revealed a contrast enhancing, paraspinal soft tissue mass in his cervical region. Microscopic examination in both the cases revealed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Some cases were reported to show active to chronic inflammatory infiltrate ( Fig. 1D and 1) (2,5,10). All cases demonstrated mild to moderate pleomorphism.…”
Section: Histopathologymentioning
confidence: 93%
See 3 more Smart Citations
“…Some cases were reported to show active to chronic inflammatory infiltrate ( Fig. 1D and 1) (2,5,10). All cases demonstrated mild to moderate pleomorphism.…”
Section: Histopathologymentioning
confidence: 93%
“…Neoplastic cells are typically negative for GFAP, desmin, and actin. Differential keratin expression of PDC is not well studied and needs to be more precisely addressed: keratins 7 and 20, which are known to be expressed in classical chordoma, were both negative in only two studied cases (2,15). Few cases have been shown to express neurofilament and galectin-3.…”
Section: Immunohistochemical Findingsmentioning
confidence: 97%
See 2 more Smart Citations
“…Decalcification of the tissue may also lead to loss of brachyury expression. Studies have reported loss of INI-1 staining in poorly differentiated chordoma, particularly in children [73][74][75][76][77][78][79][80][81].…”
Section: Pathologic Featuresmentioning
confidence: 99%